HUBUNGAN ASPEK SAFETY COMMUNICATION DENGAN SAFE WORK PRACTICES KONTRAKTOR PERBAIKAN TANKI DI PT. PERTAMINA (PERSERO) REFINERY UNIT IV CILACAP - Yuannisa, Yuannisa; Ekawati, Ekawati; Wahyuni, Ida (Jurnal Kesehatan Masyarakat (Undip), 2015)
Safety communication is one way to create a safe work practices on workers. Safe work practices must be applied to each work what aims to reduce the number of occupational accidents. Work of tank repair contractor in PT. Pertamina (Persero) Refinery Unit IV Cilacap is a high-risk job which has occurred 1 fatality in 2013. Purpose of this study is to determine the correlation among safety communication aspect and safe work practices tank repair contractor of PT. Pertamina (Persero) Refinery Unit IV Cilacap. Research method is quantitative with cross sectional approach. Sample of this study used total sampling technique, consist of 86 workers of tank repair contractor. Data analysis was done using descriptive statistic and Chi Square test (significant level 0.05). Results of the study showed that workers who implement safe work practices with safely are 93%, categorized well in socialization of K3 are 77.9%, categorized well in communication and procedures are 68.6%, and categorized well in safety program are 61.6%. Results of bivariate analysis showed that, there is a correlation among socialization K3 with safe work practices (p-value 0.020). While communication and procedures (p-value 0.373) and safety programs (p-value 0.671) there were no correlation with safe work practices. It was recommended for company that SOP enforcement toward the safe work practices of contractor workers be more assertive, and for workers be more concerned and aware about safety work messages.